Ø£Ø³Ù"ÙˆØ¨ Ø§Ù"Ø®Ø±ÙŠØ·Ø© Ø§Ù"Ø¹Ù,Ù"ÙŠØ© ÙˆØªØ·Ø¨ÙŠÙ,Ù‡ Ø¨Ø§Ù"ØµÙˆØ± Ø§Ù"ÙÙˆØªÙˆØºØ±Ø§ÙÙŠØ© Ù"ØªØ±Ù,ÙŠØ© Ù...Ù€Ù‡Ø§Ø±Ø© Ø§Ù"ÙƒÙ"Ø§Ù... ÙÙŠ Ø§Ù"Ø³ÙƒÙ† Ø§Ù"Ø¯Ø§Ø®Ù"ÙŠ Ù...Ø¬Ù...Ø¹ Ø§Ù"ÙØªÙŠØ§Ù† Ø§Ù"ØªØ¹Ù"ÙŠÙ...ÙŠ Ø£ØªØ´ÙŠÙ‡ - Yulistri Yulistri (Universitas Islam Negeri Ar-Raniry, 2015)
Learning the speaking skills in the girls' dormitory of Aceh Alfityan foundation emphasizes on memorizing a lot of vocabularies and practicing of Arabic conversation. After conducting pre observation, the researcher found that the second grade of junior high school faced a number of problems in practicing the Arabic conversation such as the difficulty in arranging the Arabic sentences in accordance with the rules. The results of this classroom action research indicated that the application of mind mapping and photographic models were effective and could help the students to improve and smarten their speaking skills. As the researcher note in their daily conversations, the students’ ability in Arabic speaking skill was better than before. The students’ response toward the learning speaking skills using mind mapping and photography models was very effective. It was based on the observation in the teaching and learning process in the classroom. The students were very delighted while learning activity and at the same time they could also improve their understanding toward the learning materials. In addition, they were be able to practice Arabic conversation skills fluently during their daily life. Moreover, the application of mind mapping and photographic models took the important role in enhancing the ability of students’ Arabic speaking skills. It was supported by the results analysis of each student’s answer in each phase. The researchers found an average increase in the students’ learning evaluation test in each phase.